Polymorphic variants of interleukin-13 R130Q, interleukin-4 T589C, interleukin-4RA I50V, and interleukin-4RA Q576R in allergic rhinitis: A pilot study - Yadav, Aravind (OceanSide Publications, Inc., 2012)
The development of allergic rhinitis is considered to be caused by the complex interactions between genetic predisposition and environmental factors. Polymorphisms in the interleukin (IL)-13/4/4RA pathway have previously been shown to be associated with atopic diseases. The purpose of this study was to determine the association between IL-13 R130Q, IL-4 T589C, IL4 receptor alpha (IL-4RA) I50V, or IL-4RA Q576R polymorphisms and risk of allergic rhinitis in a hospital-based Malaysian population. A case-control pilot study was undertaken and genotyping of these polymorphisms was performed using polymerase chain reaction–restriction fragment length polymorphism on 54 allergic rhinitis patients and 45 healthy individuals. Polymorphism of IL-13 R130Q showed significant difference in genotype (p = 0.048) and allele (p = 0.002) frequencies in allergic rhinitis when compared with healthy controls. Individuals who were GA heterozygotes (adjusted odds ratio [OR(adj)] = 3.567; 95% CI, 1.211–10.509), and carriers of A allele genotype (OR(adj) = 3.686; 95% CI, 1.300–10.451) and A allele (OR(adj) = 3.071; 95% CI, 1.514–6.232) had an elevated risk of developing allergic rhinitis. The genotype and allele frequencies of IL-4 T589C, IL-4RA I50V, and IL-4RA Q576R polymorphisms were not significantly different between the allergic rhinitis patients and normal healthy individuals and did not show an associated risk with allergic rhinitis. Our findings indicate that polymorphic variant of IL-13 R130Q appears to be associated with increased risk for development of allergic rhinitis in a hospital-based Malaysian population but not IL-4 T589C, IL-4RA I50V, and IL-4RA Q576 polymorphisms. Additional studies using larger sample size are required to confirm our findings and its exact role in allergic rhinitis.